2011
DOI: 10.1177/0146167211410355
|View full text |Cite
|
Sign up to set email alerts
|

Does Being Attractive Always Help? Positive and Negative Effects of Attractiveness on Social Decision Making

Abstract: Previous studies of organizational decision making demonstrate an abundance of positive biases directed toward highly attractive individuals. The current research, in contrast, suggests that when the person being evaluated is of the same sex as the evaluator, attractiveness hurts, rather than helps. Three experiments assessing evaluations of potential job candidates (Studies 1 and 3) and university applicants (Study 2) demonstrated positive biases toward highly attractive other-sex targets but negative biases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 72 publications
6
85
0
3
Order By: Relevance
“…We will analyze data from Ryff's ''personal relationships'' factor along with WLS data on friendships and relations with others throughout life to hone in on this question we suggest that beauty may not be an advantage on this well-being factor, particularly in a person's relationships with members of the same sex. Several studies have found that others may avoid, derogate or have negative biases toward attractive individuals of the same sex, male or female (Agthe et al 2011). …”
Section: Limitationsmentioning
confidence: 99%
“…We will analyze data from Ryff's ''personal relationships'' factor along with WLS data on friendships and relations with others throughout life to hone in on this question we suggest that beauty may not be an advantage on this well-being factor, particularly in a person's relationships with members of the same sex. Several studies have found that others may avoid, derogate or have negative biases toward attractive individuals of the same sex, male or female (Agthe et al 2011). …”
Section: Limitationsmentioning
confidence: 99%
“…Evidence for a disadvantage of beauty comes from an experimental study in which Agthe, Spörrle, and Maner (2011) found that highly attractive people are likely to receive a positive reaction from the opposite sex but a negative reaction from the same sex during job hiring or university admissions procedures.…”
Section: Beautymentioning
confidence: 99%
“…The poor treatment of attractive females by other females has been documented beyond the use of indirect aggression. For example, in the work place, women routinely discriminate against same-sex candidates, particularly attractive same-sex candidates, whereas men actively welcome such women [45,46]. When offering a request for forgiveness, women are less accepting of the apology and judge the quality of the apology as poorer when it is offered by an attractive woman than when it is offered by an unattractive woman.…”
Section: Introductionmentioning
confidence: 99%